2014
DOI: 10.30750/ijpbr.2.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Endosulphan Concentration alters biomarkers in albino rat

Abstract: Effect of 11.01ppm of endosulfan dose on the enzyme Acid phosphatase and Alkaline phosphatase in liver and kidney of 5 week of swiss albino rat was studied for different period of exposure. The enzyme activity increased due to congestion, biliary hindrance and hyperplasia swelling of renal tubules and vacuolization. Phosphatase testing is used to assess enzymatic damage caused by kidney disease, liver disease, or a heart attack. Primary site of organochlorine storage in the body is adipose tissue. It is metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Also, the change in the ACP activity may be related to the biotransformation and elimination of the tested pesticide. 35 The significant elevation in the activity of ALP indicated damage to any or all of the organs producing this enzyme such as the liver and kidney is due to leakage of lysosomal enzymes into the cytoplasm and renal necrosis and pyknotic nuclei. This result is paralleled by the result of Ambali et al 21 Rahman et al 36 suggested that the decrease in the activities of ALP and ACP in different tissues Figure 5 AST and ALT activities in different organs of male rabbits treated with 0.2 mg/kg/day for two weeks of parathion after four weeks of last treatment.…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…Also, the change in the ACP activity may be related to the biotransformation and elimination of the tested pesticide. 35 The significant elevation in the activity of ALP indicated damage to any or all of the organs producing this enzyme such as the liver and kidney is due to leakage of lysosomal enzymes into the cytoplasm and renal necrosis and pyknotic nuclei. This result is paralleled by the result of Ambali et al 21 Rahman et al 36 suggested that the decrease in the activities of ALP and ACP in different tissues Figure 5 AST and ALT activities in different organs of male rabbits treated with 0.2 mg/kg/day for two weeks of parathion after four weeks of last treatment.…”
Section: Biochemical Studiesmentioning
confidence: 99%